1975
DOI: 10.1136/sti.51.1.41
|View full text |Cite
|
Sign up to set email alerts
|

Gonorrhoea in 1972. A 1-year study of patients attending the VD Unit in Uppsala.

Abstract: During 1972 all patients visiting the Venereal Disease Clinic of the University Hospital in Uppsala were subjected to careful and extensive interrogation, and the information so obtained was adapted for computer reading, as were the results of clinical examination and microbiological tests. The aim of this programme was not only to evaluate the adequacy of current therapy and epidemiological efforts, but also to illnte problems concerned with information and attitudes. The diagnosis of gonorrhoea was made if e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1975
1975
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 8 publications
1
15
0
Order By: Relevance
“…In the literature we have found no directly comparable results, but Wallin (1975) showed that patients suffering from scabies in a VD Clinic in 1972 had a higher frequency of gonorrhoea than other venereological patients. Three studies from Danish gynaecological departments (Andersen and Nielsen, 1974;Gregersen, 1972;Hansen and Lange, 1973), showed an incidence of gonorrhoea between 1-3 and 2 8 per cent.…”
Section: Discussionmentioning
confidence: 81%
“…In the literature we have found no directly comparable results, but Wallin (1975) showed that patients suffering from scabies in a VD Clinic in 1972 had a higher frequency of gonorrhoea than other venereological patients. Three studies from Danish gynaecological departments (Andersen and Nielsen, 1974;Gregersen, 1972;Hansen and Lange, 1973), showed an incidence of gonorrhoea between 1-3 and 2 8 per cent.…”
Section: Discussionmentioning
confidence: 81%
“…It has been described in case studies and in selected groups of patients, such as homosexual men, pregnant women, and patients practising oro-genital intercourse (Fiumara et al, 1967;Owen and Hill, 1972;Pariser, 1972;Rodin et al, 1972;Courman et al, 1974;Wallin, 1974;Shahidullah, 1976;Stutz et al, 1976. ) In the present study, pharyngeal culture specimens were taken from consecutive new patients attending a city-county venereal disease clinic.…”
Section: Introductionmentioning
confidence: 99%
“…contacts of men with urethral gonorrhoea will be found to be infected (Wallin, 1974). This project was supported by a grant from the Biomedical Research Committee of the Scottish Home and Health Department (Grant No.…”
mentioning
confidence: 99%